A randomized feasibility pilot trial of a financial incentives intervention for dietary self-monitoring and weight loss in adults with obesity. Issue 4 (27th November 2020) - Voils, Corrine I; Pendergast, Jane; Hale, Sarah L; Gierisch, Jennifer M; Strawbridge, Elizabeth M; Levine, Erica; McVay, Megan A; Reed, Shelby D; Yancy, William S; Shaw, Ryan J
Abstract: Financial incentives could be used to improve adherence to behavioral weight loss interventions, increasing their effectiveness. This Phase IIb randomized pilot study evaluated the feasibility and acceptability of a study protocol for providing financial incentives for dietary self-monitoring and/or weight loss. Community-dwelling adults with obesity were enrolled in a 24 week, group-based weight loss program. Participants were randomized in a 2 × 2 factorial design to receive financial incentives for both dietary self-monitoring and weekly weight loss, just one, or neither. Participants could earn up to $300, evolving from fixed weekly payments to intermittent, variable payments. The notice of reward was provided by text message. The study was conducted in three successive cohorts to evaluate study procedure changes, including dietary approach, recruitment and retention strategies, text messaging, and incentives. Descriptive statistics calculated separately for each cohort described study performance relative to predefined targets for recruitment, including minority representation; retention; adherence; and weight loss. Acceptability was assessed via postintervention qualitative interviews. In Cohort 1 ( n = 34), a low-carbohydrate diet was used. Recruitment, retention, adherence, and weight loss were adequate, but minority representation was not. For Cohort 2 ( n = 31), employing an additional recruitment method and switching to a reduced-calorie diet yielded adequate recruitment, minority representation, retention, and adherence but less weight loss. Returning to a low-carbohydrate diet in Cohort 3 ( n = 28) yielded recruitment, minority representation, retention, adherence, and weight loss similar to Cohort 2. Participant feedback informed changes to text message timing and content and incentive amount. Through successive cohorts, we optimized recruitment and retention strategies and text messaging. An adequately powered trial is warranted to evaluate the efficacy of these incentive structures for reducing weight. The trial registration number is NCT02691260.